Study on the Microscopic Characteristics of Ferruginous cement of Banguo Earth Forest in Yuan mou area, Yunnan, China - Penghui Luo; Shitao Zhang; Yimin Tian; Fei Ding; Zongming Xu (Earth Sciences Research Journal)
The column height of earth forest is generally 8~30m in yuanmou county of yunnan province, which is far higher than the self-supporting height of general soil column. Ferruginous cement is an important reason for formation of the tall and erect columnar soil. Macroscopic physical and mechanical tests confirmed that the strength of the stratum containing ferruginous cement was much higher than that of the formation without ferruginous cement. The microstructure and morphology of ferruginous cement were analyzed by SEM and EDS. It is found that ferruginous cement is mainly composed of iron compounds and clay minerals, which only exists in certain stratum. In the process of growth, Iron compounds chemically bond with clay minerals during growth to form ferruginous cements, which first form unique sphere on the surface of particles or clay minerals. It then clumps together and fills the spaces between the particles. Finally, the dispersed particles are connected together to form a stable lamellar spatial structure, which greatly improves the strength of the soil. Through the study of ferruginous cement, the mechanism of this natural curing agent is understood, which enriches the research content in this field.